Laparoscopic conversion of omega loop gastric bypass to Roux-en-Y gastric bypass for Barrett’s esophagus: case report - U. G. Lange; Y. Moulla; M. Mehdorn; J. Tuennemann; A. Zabel-Langhennig; A. Ouaid; A. Dietrich (BMC Surgery, 2022)
Abstract Background The number of mini gastric bypass / one anastomosis bypass (MGB-OAGB) procedures in bariatric patients that have been performed world-wide has drastically increased during the past decade. Nevertheless, due to the risk of subsequent biliary reflux and development of ulcer and neoplastic (pre)lesions caused by long-time bile exposure, the procedure is still controversially discussed. In here presented case report, we could endoscopically demonstrate a transformation from reflux oesophagitis to Barrett’s metaplasia most likely caused by bile reflux after mini-gastric bypass. To our knowledge, this is a first case study that shows development of Barrett’s metaplasia after MGB-OAGB. Case presentation We present the case of a 50-year-old female which received a mini-gastric bypass due to morbid obesity (body mass index (BMI) 42.4 kg/m2). Because of history gastroesophageal reflux disease (GERD), a fundoplication had been performed earlier. Preoperative gastroscopy showed reflux esophagitis (Los Angeles classification grade B) with no signs of Barrett’s metaplasia. Three months post mini-gastric bypass, the patient complained about severe bile reflux under 40 mg pantoprazole daily. Six months postoperative, Endoscopically Barrett’s epithelium was detected and histopathologically confirmed (C1M0 after Prague classification). A conversion into Roux-en-Y gastric bypass was performed. The postoperative course was without complications. In a follow up after 6 months the patient denied reflux and showed no signs of malnutrition. Conclusions The rapid progress from inflammatory changes of the distal esophagus towards Barrett’s metaplasia under bile reflux in our case is most likely a result of previous reflux disease. Nevertheless, bile reflux appears to be a potential decisive factor. Study results regarding presence of bile reflux or development of endoscopically de-novo findings after MGB-OAGB are widely non-conclusive. Long-term prospective studies with regular endoscopic surveillance independent of clinical symptoms are needed.